Maternal supplementation with citrulline or arginine during gestation impacts fetal amino acid availability in a model of intrauterine growth restriction (IUGR). Issue 12 (December 2020) - Bourdon, Aurélie; Hannigsberg, Jacob; Misbert, Emilie; Tran, Thang Nhat; Amarger, Valérie; Ferchaud-Roucher, Véronique; Winer, Norbert; Darmaun, Dominique
Summary: Background: Supplementing maternal diet with citrulline or arginine during gestation was shown to enhance fetal growth in a model of IUGR induced by maternal dietary protein restriction in the rat. Objective: The aims of this study were to determine in the same model whether maternal supplementation with citrulline or arginine would increase 1) citrulline and arginine concentration in fetal circulation; 2) the expression of placental amino acid transporters, and 3) the fetal availability of essential amino acids. Methods: Pregnant rats (n = 8 per group) were fed either an isocaloric control (20% protein, NP) or a low protein (LP, 4% protein) diet, either alone or supplemented with 2 g/kg/d of l -citrulline (LP + CIT) or isonitrogenous Arginine (LP + ARG) in drinking water throughout gestation. Fetuses were extracted by C-section on the 21st day of gestation. The gene expression of system A ( Slc38a1, Slc38a2, and Slc38a4 ) and L ( Slc7a2, Slc7a5, Slc7a8 ) amino acid transporters was measured in placenta and amino acid concentrations determined in maternal and fetal plasma. Results: Maternal LP diet decreased fetal (4.01 ± 0.03 vs. 5.45 ± 0.07 g, p < 0.0001) and placental weight (0.617 ± 0.01 vs. 0.392 ± 0.04 g, p < 0.001), by 26 and 36% respectively, compared with NP diet. Supplementation with either CIT or ARG increased fetal birth weight by ≈ 5 or 11%, respectively (4.21 ± 0.05 and 4.48 ± 0.05 g vs. 4.01 ± 0.03 g, p < 0.05). CIT supplementation produced a 5- and 2-fold increase in fetal plasma citrulline and arginine, respectively, whereas ARG supplementation only increased fetal arginine concentration. LP diet led to lower placental SNAT 4 mRNA, and higher LAT2 and SNAT1 expression, compared with NP. SNAT4, 4hFC, LAT2 mRNA were up-regulated in LP + CIT and LP + ARG group compared with the un-supplemented LP group. Higher level of LAT1 mRNA was also observed in the LP + CIT group than in the LP group (p < 0.01). SNAT2 expression was unchanged in response to CIT or ARG supplementation. Fetal amino acid concentrations were decreased by LP diet, and were not restored by CIT or ARG supplementation. Conclusions: The current findings confirm supplementation with citrulline or arginine enhances fetal growth in a rat model of IUGR. They further suggest that: 1) citrulline and arginine administered orally to the pregnant mother may reach fetal circulation; 2) citrulline effectively raises fetal arginine availability; and 3) although it failed to increase the concentrations of essential amino acids in fetal plasma, citrulline or arginine supplementation upregulates the gene expression of several placental amino acid transporters.